Research on the Construction of a New Ecological Environment for Tourism Major Education in Higher Vocational Colleges - Wen, Xinli; Li, Boil (Journal of Roi Kaensarn Academi, 2023)
This research aims to explore whether the teaching ability and quality of vocational tourism teachers have an impact on the new ecology of tourism education. Teachers and students in the tourism major of a vocational college in Chongqing, China, were selected as the targets of this research. Based on the relevant literature, two hypotheses are proposed. The data was collected through online questionnaires, and statistical tests were conducted using SPSS22.0 and AMOS24.0 software. The statistical tests included descriptive statistical analysis, reliability and validity testing of test items, model fitting testing, and research hypothesis testing. The research results found that the abilities and qualities of vocational tourism teachers have a positive impact on the new ecology of tourism education. Finally, based on the research findings, corresponding research recommendations were proposed.